1993
DOI: 10.1021/ja00079a043
|View full text |Cite
|
Sign up to set email alerts
|

Arranging quaternary structure of peptides by cyclodextrin-guest inclusion complex: sequence-specific DNA binding by a peptide dimer with artificial dimerization module

Abstract: Arranging quaternary structures by dimerization of monomers is necessary for many sequence-specific DNA-binding proteins to become functional. Upon dimer formation, the DNA contacting regions of each monomer are positioned to a proper orientation that facilitates efficient sequence-specific recognition of DNA.1 Several laboratories have reported model studies that demonstrate the importance of such steric constraints by using covalently bonded dimeric peptides.* 12 However, natural proteins dimerize with nonco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 0 publications
5
67
1
Order By: Relevance
“…These molecular recognitions have been mainly studied by gel mobility shift assay. [1][2][3][4][5] This technique is widely used in molecular biology; however, it has some difficulties with regard to quantitatively detecting interactions. DNA or peptide is usually labeled either directly or indirectly with fluorescent or radioactive molecules, and it takes relatively a long time to analyze the results.…”
Section: Introductionmentioning
confidence: 99%
“…These molecular recognitions have been mainly studied by gel mobility shift assay. [1][2][3][4][5] This technique is widely used in molecular biology; however, it has some difficulties with regard to quantitatively detecting interactions. DNA or peptide is usually labeled either directly or indirectly with fluorescent or radioactive molecules, and it takes relatively a long time to analyze the results.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly relevant are those based on dimeric bZIP basic regions, in which the natural C/C-terminal leucine zipper is replaced by artificial dimerizers [14][15][16][17] . Some of these designs have gone even further and incorporate switchable elements that allow conditional off/on DNA binding by the application of external stimuli such as light or metal ions [18][19][20][21][22] .…”
mentioning
confidence: 99%
“…Building on this successful idea of miniaturisation, Morii, Schepartz, Mascareñas Q3 and our group have enforced the proof-of-concept by using a variety of small dimerizing moieties. [7][8][9][10][11][12] Subsequently, we have shown that the attachment of the basic region peptides to a rigid scaffold, a derivative of deoxycholic acid in this case, also allows selective recognition of DNA. Indeed, our previous work on cMyc-Max b-HLH-ZIP and GCN4-bZIP proteins showed that this type of steroid-based constructs show potential for binding DNA.…”
Section: Q4mentioning
confidence: 99%